Investigation of erythrocyte cholinesterase inhibition and liver toxicity by artificial fruit ripener Ethereal in vivo - Chathuranga, T.T.D; Peiris, L.D.C (Wulfenia Journal, 2020)
A novel liquid plant growth regulator dubbed ethereal (ET) employed primarily for artificial fruit ripening has been deemed a systemic health concern with documented reports of severe hepatotoxicity. The present study evaluated the viability of the use of Wistar rats (Rattus norvegicus) as valid test model for human acetylcholinesterase (AChE) through computational phylogenetics followed by investigation of the ET toxicity using male Wistar rats. The adverse effects were studied using a population of 36 male rats (n=9) who were orally treated either with 100, 250, 500 mg/kg of ET or Distilled Water (DW: Control) for 90 days. The reversible effects and delayed toxicity from ET exposure was studied using two separate sets of animals (n=6) who were gavaged with 500 mg/kg of ET and DW for 90 days (main group) and kept for another 28 days without treatment (recovery group). On days 91 and 119 erythrocyte cholinesterase (EChE), which is homologous to AChE and liver toxicity (ALT and AST levels) were determined. Treatment with ET induced a significant inhibition of EChE at both 250, 500 mg/kg groups and also in the recovery group. exploratory behaviour parameters, muscle strength and coordination, However, ET had Similar results were observed with ALT, AST levels both main and recovery groups. These effects were also evident by liver histopathology. It can be concluded that continuous exposure to ethrel could induce liver toxicity and alteration in EChE activity even after withdrawal from exposure.
Keywords: Fruit ripener, ethrel, ethephon, ALT, AST, erythrocyte cholinesterase acetylcholine esterase